2006
DOI: 10.1086/506147
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of the Blue Wing Enhancements in the High-Ionization Lines of SDSS 1004+4112A

Abstract: We present integral field spectroscopic observations of the quadruple-lensed QSO SDSS 1004+4112 taken with the fiber system INTEGRAL at the William Herschel Telescope on 2004 January 19. In May 2003 a blueward enhancement in the high ionization lines of SDSS 1004+4112A was detected and then faded. Our observations are the first to note a second event of similar characteristics less than one year after. Although initially attributed to microlensing, the resemblance among the spectra of both events and the absen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 22 publications
3
33
0
Order By: Relevance
“…The second season shows no obvious features that can be used to measure the delay. The second important point to note is that the A / B flux ratio has changed significantly between the first and third seasons, indicating that microlensing is occurring in this system as has been previously suggested by variations in the C iv emission-line profile (Richards et al 2004;Lamer et al 2006;Gómez-Á lvarez et al 2006 within each season of the light curves. Of the many techniques for calculating time delays from light curves (e.g., Gil-Merino et al 2002;Pelt et al 1994;Press et al 1992;Kochanek et al 2006a), we apply three.…”
Section: Datamentioning
confidence: 54%
See 2 more Smart Citations
“…The second season shows no obvious features that can be used to measure the delay. The second important point to note is that the A / B flux ratio has changed significantly between the first and third seasons, indicating that microlensing is occurring in this system as has been previously suggested by variations in the C iv emission-line profile (Richards et al 2004;Lamer et al 2006;Gómez-Á lvarez et al 2006 within each season of the light curves. Of the many techniques for calculating time delays from light curves (e.g., Gil-Merino et al 2002;Pelt et al 1994;Press et al 1992;Kochanek et al 2006a), we apply three.…”
Section: Datamentioning
confidence: 54%
“…This result provides strong evidence that the differential changes in the A/ B emission line profiles are also due to microlensing ( Richards et al 2004;Lamer et al 2006;Gómez-Á lvarez et al 2006) rather than variable absorption in the source (Green 2006). The microlensing timescales in SDSS J1004+4112 should be relatively shorter than in most single galaxy lenses because the internal velocities of the cluster are about 3 times higher than those of a galaxy.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Abajas et al (2002) have estimated which gravitational lens systems are more likely to show BLR changes due to microlensing. Some examples of these variations in the BLR have been presented by Filippenko (1989), Chartas et al (2002), Chartas et al (2004), Richards et al (2004), Gómez-Álvarez et al (2006), and Sluse et al (2011) in the cases of MG0414+0534, H1413+117, SDSS1004+4112, and Q2237+0305.…”
Section: Continuum Microlensing Measurementmentioning
confidence: 99%
“…Richards et al (2004) found enhancement of the blue wings of some emission lines in SDSS J1004+4112 that were attributed to microlensing. The blue wing enhancement was also observed by Gómez‐Álvarez et al (2006), but the absence of other microlensing‐induced changes suggested that intrinsic variability may be the cause. The latter has been supported by Lamer et al (2006), who suggest it provides a better explanation than microlensing for differences in X‐ray and ultraviolet variability.…”
Section: Introductionmentioning
confidence: 84%